2020
DOI: 10.1002/pc.25848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing parameters for vacuum‐bag‐only method on void content and mechanical properties of laminated composites

Abstract: Process parameters for vacuum‐bag‐only (VBO) method are of critical importance to control manufacturing‐induced void content and mechanical properties of laminated composites. Currently, no comparative studies are readily available on various VBO processing parameters namely bagging techniques, cure cycles, and laminate thicknesses on induced defects and mechanical properties. Hence, this study investigates the effects of these parameters on manufacturing‐induced void content and mechanical properties of compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Moreover, the burn‐off method yielded more consistent V f results for all laminate types, and also in general greater consistency with the measured material densities (i.e., higher V f corresponded to higher material densities). The average void content of unconditioned [0°] 16 laminates was 2.84%; this level is consistent with values obtained by Chu et al [ 62 ] and the trend found by Mujahid et al [ 63 ] for high V f laminates. The average thickness of conditioned in‐plane shear specimens was slightly lower than unconditioned specimens.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the burn‐off method yielded more consistent V f results for all laminate types, and also in general greater consistency with the measured material densities (i.e., higher V f corresponded to higher material densities). The average void content of unconditioned [0°] 16 laminates was 2.84%; this level is consistent with values obtained by Chu et al [ 62 ] and the trend found by Mujahid et al [ 63 ] for high V f laminates. The average thickness of conditioned in‐plane shear specimens was slightly lower than unconditioned specimens.…”
Section: Resultssupporting
confidence: 91%
“…After that, the nylon peel ply and breather cloth are placed one over the other. [ 54 ] Then it shifted to a thin polymer film attached to a vacuum pump. After that, the bag has fully sealed using a sealant tape.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…An increase in compressive strength and reduced shrinkage was achieved by using MWCNTs as nanoreinforcements in hybrid epoxy composites (MWCNT/silica fume cement). The compressive properties of hybrid polymer composites are also improved when MWCNTs are included [29]. Furthermore, it is necessary to do further research into the mechanical and tribological properties of carbon nanotubebased hybrid composite materials.…”
Section: Introductionmentioning
confidence: 99%